2020
DOI: 10.1177/0308575920902598
|View full text |Cite
|
Sign up to set email alerts
|

Being adopted and being a mother

Abstract: Twenty-one women adopted as infants within the Australian state of Victoria discussed their lived experience as mothers and the impacts of their adoption at this life stage. Sixteen participants took part in semi-structured interviews and the emerging categories were evaluated by a focus group of five additional adopted women. While each of their accounts is unique, reflecting their own individual life histories, partnerships and social networks, shared threads of meaning run through the combined narratives. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Second, as in prior research (e.g., Conrick, 2020) our study suggests that that when people with a history of care become parents, they enter into a period of life review about their past experiences and a re-evaluation and updating of their sense of self. For example, the mothers in our sample described how having a biological relative in their lives engendered a greater sense of 'completeness'.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Second, as in prior research (e.g., Conrick, 2020) our study suggests that that when people with a history of care become parents, they enter into a period of life review about their past experiences and a re-evaluation and updating of their sense of self. For example, the mothers in our sample described how having a biological relative in their lives engendered a greater sense of 'completeness'.…”
Section: Discussionsupporting
confidence: 64%
“…In doing so, such studies have highlighted several positive and negative experiences related to becoming a parent. On the positive side, becoming a parent as an adoptee can provide an opportunity to reflect on one’s own identity (e.g., Conrick, 2020). In particular, this transition can evoke a new interest in one’s own genealogy (e.g., Pinkerton, 2010) and can provide a deeper layer of meaning whereby adopted parents integrate their biological and adopted origins (Pinkerton, 2010; Battalen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Conrick's (2020) study, adoptee women reported feeling like an outsider in adoptive families and being treated differently than their siblings as children. Children who have experienced loss, neglect and maltreatment are more likely to experience feelings of mistrust and abandonment (Burnell et al, 2009).…”
Section: Struggled To Fit In and Feel Like I Had A Place Within That ...mentioning
confidence: 96%